Methanol‐based cadaverine production by genetically engineered Bacillus methanolicus strains. Issue 2 (23rd January 2015) - Nærdal, Ingemar; Pfeifenschneider, Johannes; Brautaset, Trygve; Wendisch, Volker F.
Summary Methanol is regarded as an attractive substrate for biotechnological production of value‐added bulk products, such as amino acids and polyamines. In the present study, the methylotrophic and thermophilic bacterium Bacillus methanolicus was engineered into a microbial cell factory for the production of the platform chemical 1, 5‐diaminopentane (cadaverine) from methanol. This was achieved by the heterologous expression of the Escherichia coli genes cadA and ldcC encoding two different lysine decarboxylase enzymes, and by increasing the overall L‐lysine production levels in this host. Both CadA and LdcC were functional in B. methanolicus cultivated at 50°C and expression of cadA resulted in cadaverine production levels up to 500 mg l−1 during shake flask conditions. A volume‐corrected concentration of 11.3 g l−1 of cadaverine was obtained by high‐cell density fed‐batch methanol fermentation. Our results demonstrated that efficient conversion of L‐lysine into cadaverine presumably has severe effects on feedback regulation of the L‐lysine biosynthetic pathway in B. methanolicus. By also investigating the cadaverine tolerance level, B. methanolicus proved to be an exciting alternative host and comparable to the well‐known bacterial hosts E. coli and Corynebacterium glutamicum. This study represents the first demonstration of microbial production of cadaverine from methanol.